Analisis Status Pekerja, Kompetensi Karyawan dan Budaya Kerja terhadap Kinerja Karyawan PT. Mitra Pinasthika Mulia Surabaya - Hamy Wahjunianto; Sulastri Sulastri (Sekolah Tinggi Ilmu Ekonomi Yapan, 2022)
This study aims to determine whether the variables of employee status, employee competence and work culture simultaneously have a significant effect on the performance of employees of PT. Mitra Pinasthika Mulia Surabaya. Data collection techniques were carried out through questionnaires, interviews, and observations, which consisted of primary data and secondary data. Furthermore, the data were analyzed quantitatively, using statistical models in the SPSS 22.00 program, with descriptive analysis techniques and multiple linear regression analysis. The results showed that: There was a simultaneous (simultaneous) independent variable in the form of worker status, competence and work culture on the dependent variable, namely employee performance at PT. Mitra Pinasthika Mulia Surabaya, Based on the results of the t-test calculations carried out, it can be seen that the independent variables in the form of worker status, competence and work culture partially have a significant effect on the dependent variable, namely the performance of employees at PT. Mitra Pinasthika Mulia Surabaya.